Left Ventricular Dyssynchrony Predicts Clinical Response to CRT – A Long‐Term Follow‐Up Single‐Center Prospective Observational Cohort Study. Issue 8 (12th March 2013) - Prinz, Christian; Lehmann, Roman; Schwarz, Maria; Prinz, Eva‐Maria; Bitter, Thomas; Vogt, Jürgen; van, Frank; Bogunovic, Nikola; Lamp, Barbara; Horstkotte, Dieter; Faber, Lothar
<x xml:space="preserve">Abstract</x> Background Until now, there is no consensus regarding the definition of a clinical response to cardiac resynchronization therapy (CRT) in patients with chronic heart failure (CHF) and systolic left ventricular (LV) dysfunction. The aim of this study was to evaluate if echocardiography is predictive for an objective improvement in exercise capacity during long‐term follow‐up of CRT. Methods Each patient underwent echocardiography and spiroergometry both at baseline and at last follow‐up. Left ventricular dyssynchrony (LVD) before CRT was defined by tissue Doppler imaging (TDI) as intra‐LV delay ≥40 msec (septal‐lateral or anterior‐posterior). Clinical response to CRT was defined as increase of peakVO2 or as increase of maximal workload >10% as compared to baseline. Results Mean follow‐up was 69 ± 37 months. From the 238 consecutive patients included in the study, 141 (59%) were classified as clinical responders and 97 (41%) as nonresponders. Baseline data of responders and nonresponders were comparable. However, clinical responders showed more often LVD (64%) than nonresponders (42%, P = 0.004). On multivariate regression analysis, nonischemic origin of CHF (β‐coefficient in the final model 0.1, P = 0.04) and LVD at baseline (β‐coefficient in the final model 0.2, P < 0.001) were independently associated with clinical response during long‐term follow‐up. Patients with LVD at baseline had significant more often an improvement of left ventricular ejection fraction >10% (P = 0.02) and a reduction of left ventricular end‐diastolic diameter (LVEDD) >10% (P < 0.01) than patients without LVD at baseline. Conclusions LVD at baseline as assessed by a straightforward echocardiographic approach predicts the long‐term clinical response to CRT and is associated with a more pronounced reverse LV remodeling.